The Association Between Environmental Perchlorate, Nitrate, and Thiocyanate Exposure and Oral Pain in NHANES - Yu, Jintao; Guo, Jiawen; Zhang, Hengguo; Cheng, Xu (Frontiers in Public Health, 2022)
Aim To examine the human exposure to perchlorate, nitrate, and thiocyanate, and their associations with oral pain (OP) in the general population from the U.S. Methods A total of 13,554 participants were enrolled in the National Health and Nutrition Examination Survey. The urinary perchlorate, nitrate, and thiocyanate were measured using ion chromatography coupled with an electrospray tandem mass spectrometry. The multivariable linear and logistic regressions were performed to explore the associations of the urinary perchlorate, nitrate, and thiocyanate, with the prevalence of oral pain. Restricted cubic splines were used to explore the non-linearity. Results There are 3,129 OP cases. There was a higher urinary level of perchlorate, nitrate, and thiocyanate in OP. We found that urinary thiocyanate was positively associated with OP (odds ratio [OR] = 1.06; [1, 1.13]; p = 0.049). Restricted cubic spines revealed that urinary thiocyanate was in a U-shape association with OP. Conclusions Urinary thiocyanate was in a U-shape association with OP, suggesting that we should keep the exposure of thiocyanate under a reasonable range.